Study on lighting in office buildings Kuching area - Faizal, Abd. Rahman (Universiti Malaysia Sarawak, UNIMAS, 2004)
This project is a preliminary research on lighting in office buildings Kuching area. The main aim of the project is to conduct a survey on lighting systems and consumption characteristics.